A Formal Model of text annotation based on XML entities - Geci, Branko; Bekavac, Božo (2005)
The paper proposed an annotation framework (annotation formalism) based on XML entities.analysis of the annotation proposed was made by means of a series of simulations that include XML and DTD test file generation, based on XML fragments and time measurements (durations of loading of test files into the XML parser).
Projekt MZOS
ENG